(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تمت دراسة بحث تأثير جاذبية مجرة درب التبانة على عينة عشوائية من المذنبات حيث تبلغ تعدادها حوالي 2000 مذنب, أخذت معطيات المذنبات الابتدائية بشكل عشوائي ، ثم تم إجراء عملية مكاملة معادلات الحركة لكل منها بشكل عددي تراجعياَ ، ثم تقدمياً بالنسبة للزمن. لقد تبين أن تأثير جاذبية المجرة على تطور حركة هذه العينة من المذنبات ، يلعب دوراَ هاماَ في تفسير فرضية منشأ المذنبات ، وعلاقتها بغيمة Oort المذنبية. We studied The Effect Of The Galaxy by adopting, 2000 Of Random ensemble Of Comets. The initial orbital elements were chosen by Random. The Equations Of motion Of The Comets were integrated backward and forward by numerical integrations according to the time. It was obvious that the Galactic tide was more important of the devolopment of this ensemple of Comets to explain hypothetical origin of Comets and it,s Relation with Oort Cloud.